A Linear Programming Model for Optimizing Resources Within a Factory - ADEDUGBA adebayo. T; OGUNNAIKE olaleke O; ADEYEMO Kingsley A; KEHINDE busola E (Communications of International Proceedings, 2021)
The major goal of any organization is the need to meet the expectation of client’s within the stipulated period of request. The expectation of customers can only be met if the products or services are designed at a high quality with a low cost to the end user or customer.The production of goods and services should be at a minimal cost i.e minimal wastage of materials. The objective is the identification of an optimal distribution of resources in other to maximize profit and lower cost within the framework. The lower the wastage of resources the more resources available for usage. The study applied linear programming using linear programming software(Lips) and the analysis showed that X1=35 units, X2=75 units, and X3 = 0 units of various wood sizes will be produced to make an optimal profit of 110. To maximize profit amidst scares resources more of X1 and X2 should be produced.
Keywords: Resources; Linear Programming; Optimal; Model